Strategies for Teaching the Arabic Language in light of its characteristics and social functions - Al-Selmy, Azhar nahar; Al-Awadi, Wafa Hafez (Journal of Educational and Psychological Sciences, 2022)
The study entitled Strategies for Teaching the Arabic Language in light of its characteristics and social functions, as this study consisted of an introduction in which it was presented about the importance of the Arabic language, and what are the duties imposed on the Arabic language teacher, and his knowledge of modern strategies for learning, and then presented in the introduction the problem of the study towards reasons Choosing the topic and its importance, and some previous studies that I used in my study, then the objectives through which the study was carried out, which are:- Determine the nature of the Arabic language.- Determine the Arabic language functions.- Explain the characteristics of the Arabic language.- Describe the strategies of the Arabic language in light of its social characteristics and functions.Then I talked in the topic about the definition of the Arabic language, speaking about the characteristics of the Arabic language, and I linked these characteristics to the strategies that can be applied and employ these characteristics through them. Then I presented the functions of the Arabic language explaining the role and position of the Arabic language for the individual and for society, then I explained the best methods To teach the Arabic language represented by the flexible integrative method, then I talked about the teaching method represented in concept maps, the hot chair, the story, inductive teaching, the modified text method, and then at the end I presented the results of the study, which are:- The status of the Arabic language, and that it is a language that has characteristics that other living languages ​​have not represented in foreign languages.- The need to find alternative solutions to the linguistic invasion that arose through cultural exchange, which led to dependence on the Arabic language more than any other language, then a set of proposals and recommendations, then a list of sources and references that I relied on in my study, and then an index of the topics mentioned in the study.
Keywords: Strategies; Arabic Language; Social; Teaching